Pulmonary tuberculosis: Hematology, serum biochemistry and the relation with the disease duration - Oliva, V. M. [UNESP]; Cezário, G. A.G. [UNESP]; Cocato, R. A. [UNESP]; Marcondes-Machado, Jussara [UNESP] (My University, 2008)
The aim of the present study was to analyze the relationship between hematological and biochemical parameters and tuberculosis process activity time according to clinical complaint duration. It was a retrospective study analyzing medical records from 80 pulmonary tuberculosis patients at Botucatu Medical School University Hospital (Botucatu, São Paulo State, Brazil), who were divided into 2 groups according to clinical complaint duration: Group 1 (G1) - up to three months; Group 2 (G2) - over three months. Parameters included: age, gender, bacilloscopy, erythrocyte sedimentation rate (ESR), platelet count, alpha1-globulin, alpha2-globulin, gamma globulin, mucoprotein, alpha1-acid glycoprotein values, and the presence of risk factors such as smoking, alcoholism, drug addiction, sexual promiscuity, contact with tuberculosis carriers, and previous treatment. Groups were compared by calculating t and p, and Chi-square (X2) and p. Comparisons revealed a tendency towards smoking with a higher frequency of smokers in G1 (0.05<p<0.10). G1 also tended to present greater platelet values than G2 (0.05<p<0.10) and presented significantly higher ESR values than G2 (p<0.05). Other factors did not show any significantly different behavior between groups (p>0.05). A correlation was found between ESR, platelet count, smoking and less than three months clinical duration.
Keywords: Erythrocyte sedimentation rate; Hematolological and biochemical parameters; Mycobacterium tuberculosis; Pulmonary tuberculosis; Smoking